Characterization of the T-dependent antibody response (TDAR) to keyhole limpet hemocyanin (KLH) in the Göttingen minipig. (October 2014) - Peachee, Vanessa L.; Smith, Matthew J.; Beck, Melissa J.; Stump, Donald G.; White, Kimber L.
Abstract Recently, there has been a renewed interest in the use of the minipig as an alternative to dogs and non-human primates for conducting toxicological assessments in non-rodent species. Since the T-dependent antibody response (TDAR) is one of the most widely-accepted assays used in the assessment of immunocompetence, the present study was undertaken to characterize the primary and secondary TDAR to keyhole limpet hemocyanin (KLH) in the Göttingen Minipig®. Following primary immunization with either 2 or 10 mg KLH, anti-swine IgM and IgG ELISAs were optimized and individual animal responses were evaluated over time. Immunization with 10 mg KLH on Day 0 promoted primary IgM responses that peaked 6–9 days after antigen administration, while primary IgG levels peaked on Day 13 or 14. Secondary IgG antibody levels (following secondary injection with 2 mg KLH on Day 14) plateaued on Days 20–22. Anti-KLH antibody levels were decreased in minipigs treated with cyclophosphamide (CPS), a known immunosuppressant, at doses ranging from 12.5–50 mg/kg/day, while antibody levels in animals treated with 2.5 mg CPS/kg/day were similar to levels in saline-treated swine. These results demonstrate that the Göttingen Minipig® can be a useful alternative non-rodent species to the dog and the non-human primate for evaluating the TDAR to KLH in regulatory assessments of immunotoxicity.